Respuesta :

9514 1404 393

Answer:

  f(x) = x² +3

Step-by-step explanation:

The transformation

  g(x) = a·f((x -c)/b) +d

represents a vertical expansion by a factor of 'a', a horizontal expansion by a factor of 'b' (before the horizontal shift), a horizontal (right) shift by 'c' units, and an upward shift by 'd' units.

You want only an upward shift of 3, so ...

  g(x) = f(x) +3

For f(x) = x^2, the shifted function is ...

  f(x) = x^2 +3

__

Other choices are ...

  b. (x -3)^2 = right shift by 3

  c. 3x^2 = vertical expansion by a factor of 3

  d. (x +3)^2 = left shift by 3